Microphotochemistry Using 5-mm Light-Emitting Diodes: Energy-Efficient Photooxidations - Carney, John M.; Hammer, Reagan J.; Hulce, Martin; Lomas, Chad M.; Miyashiro, Dayna (Synthesis, 2012)
Commercial, inexpensive 5-mm milliwatt light-emitting diodes are effective sources for batch microphotochemical oxidations. Using limited quantities of singlet oxygen, these oxidations are atom economical and therefore useful for labeling experiments with rare isotopes.
Keywords: photooxidation; arenes; peroxides; photoreactors; light-emitting diodes